[OP.5D.02] TRANSCRIPTOMIC CHANGES IN EARLY PREGNANCY-ASSOCIATED UTERINE ARTERY REMODELLING IN STROKE PRONE SPONTANEOUSLY HYPERTENSIVE RAT. (September 2016) - MORGAN, H.; Small, H.Y.; Beattie, E.; McBride, M.W.; Graham, D.
Abstract : Objective: Deficient spiral artery remodelling is an early gestational defect linked to a number of pregnancy complications such as pre-eclampsia and gestational hypertension. We have previously demonstrated abnormal uterine artery remodelling at gestational day 18 in the stroke prone spontaneously hypertensive (SHRSP) rat. In this study, we examined the early uterine artery structural and functional changes in SHRSP and normotensive Wistar Kyoto (WKY) rats alongside changes in the transcriptome profile. Design and method: Female SHRSP and female WKY rats were time mated at 12 weeks of age ± 4 days. At gestational day 6 (GD6) uterine arteries were dissected and pressure and wire myography performed to assess vascular structure and functional properties. RNAseq (Illumina platform; ribosome depleted, 50 million reads) was performed in uterine arteries from SHRSP and WKY at GD6 and from non-pregnant rats. RNAseq data (FDR < 0.05, FPKM > 1.0) was interpreted using Ingenuity® Pathway Analysis. Results: No significant structural or functional differences were observed in uterine arteries from SHRSP and WKY rats at GD6; cross-sectional area (57.7 ± 1.2 × 103 μm 2 vs 67.5 ± 4.2 × 103 μm 2 ), maximal constriction to noradrenaline (41.7 ± 8.1 kPa vs 49.5 ± 9.4 kPa), vasorelaxation to carbachol (76.1 ± 3.9% vs 82.2 ± 3.2%) and SNP (60.5 ± 6.2% vs 58.9 ± 5.8%) (% of maximum constriction) for WKY and SHRSP respectively. RNAseq conducted at GD6, prior to vascular remodelling or functional changes, identified 551 differentially expressed genes between pregnant WKY and pregnant SHRSP; including genes involved in uterine artery vasculogenesis (p-value = 3.78 × 10 −10 ), e.g. angiotensinogen (3.2 fold change, (fc)); angiogenesis (p-value = 3.10 × 10 −11 ), e.g. thrombospondin 4 (4.9 fc); endothelial cell proliferation (p-value = 3.94 × 10 −8 ), e.g. vascular endothelial growth factor D (2.1 fc); and the endothelial nitric oxide synthase pathway (p-value = 3.16 × 10 −4 ), e.g. ryanodine receptor 2 (2.0 fc). Pregnancy resulted in SHRSP-specific increase in expression of NADPH oxidase regulatory subunits p47phox (2.1 fc), p67phox (2.0 fc), p40phox (2.9 fc) p22phox (1.8 fc) and gp91phox (1.8 fc). Conclusions: Uterine artery gene expression during early pregnancy is markedly different between SHRSP and WKY prior to any observed functional and structural changes. Transcriptome profiling implicates pathogenic changes in vasculogenesis and angiogenesis pathways, and endothelial dysfunction, as well as evidence of abnormal oxidative stress response in SHRSP uterine arteries.